2015
DOI: 10.3727/096368913x676925
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Neurosphere Formation in Neural Stem/Progenitor Cells by Acrylamide

Abstract: Previous studies showed that transplantation of cultured neural stem/progenitor cells (NSPCs) could improve functional recovery for various neurological diseases. This study aims to develop a stem cell-based model for predictive toxicology of development in the neurological system after acrylamide exposure. Treatment of mouse (KT98/F1B-GFP) and human (U-1240 MG/F1B-GFP) NSPCs with 0.5 mM acrylamide resulted in the inhibition of neurosphere formation (definition of self-renewal ability in NSPCs), but not inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
(99 reference statements)
0
2
0
Order By: Relevance
“…Previously, the researchers found that ACR-treated neurospheres of KT98/F1B-GFP showed decrease in phosphorylated AKT through analyzing AKT pathway. 33 At the same time, extracellular TAU induces angiogenesis by activating AKT-dependent signal pathways. 10 TAU promotes cognitive function of prenatally stressed juvenile rats by activating the AKT-CREB-PGC1α pathway, 34 proving that the level of phosphorylated AKT when the rats or the cells treated with TAU.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the researchers found that ACR-treated neurospheres of KT98/F1B-GFP showed decrease in phosphorylated AKT through analyzing AKT pathway. 33 At the same time, extracellular TAU induces angiogenesis by activating AKT-dependent signal pathways. 10 TAU promotes cognitive function of prenatally stressed juvenile rats by activating the AKT-CREB-PGC1α pathway, 34 proving that the level of phosphorylated AKT when the rats or the cells treated with TAU.…”
Section: Discussionmentioning
confidence: 99%
“…1F), which indicated that FAM19A1 is expressed in NSCs and may be associated with the functions of NSCs. Neurospheres were induced to proliferate and were able to generate the 3 major phenotypes of the mammalian CNS: neurons, astrocytes, and oligodendrocytes (26,27); thus, the properties of neurospheres are frequently used as a standard by which to evaluate the abilities of NSCs (28). We then separated primary murine neurospheres from the mouse embryonic brain and demonstrated the expression and secretion of FAM19A1 in NSCs via cell immunofluorescence and the cytometric bead system (Fig.…”
Section: Fam19a1 Inhibits the Proliferation And Self-renewal Of Murinmentioning
confidence: 99%
“…In addition, glycoalkaloids can cause inflammatory bowel disease (IBD) in the mammalian intestine by destroying the intestinal epithelial barrier if excessively fried potatoes or potato skin are consumed [56,57]. Glycoalkaloids have anticarcinogenic and antiproliferative properties that inhibit the proliferation of cancer and normal cells [32,[58][59][60][61][62]. Unfortunately, this function of glycoalkaloids is detrimental to normal cells and organisms that ingest foods containing higher levels of glycoalkaloids.…”
Section: Discussionmentioning
confidence: 99%